Double-Blind, Randomized, Placebo-Controlled Clinical Trial Evaluating the Effect of Antioxidants on DNA Fragmentation Index in Men with Idiopathic Oligoasthenoteratozoospermia - Patki, Ameet; Shelatkar, Rohit; Singh, Monica; Agarwal, Sweta; M, Venugopal; Umbardand, Shashikant; Reddy, Apoorva; Kannan, Priya; Gorthi, Srilatha; Khastgir, Gautam; et al. (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Oxidative stress, sperm apoptosis, and DNA fragmentation are significant factors in male infertility. Sperm DNA damage is associated with reduced fertility and increased frequency of spontaneous abortions and affects embryo quality. Spermatogenesis is an energy-intensive process, it requires a highly balanced supply of minerals, antioxidants, and nutrients. Hence, food supplementation is thought to be a potential therapeutic option that may improve seminal fluid conditions, provide energy to male germ cells, and protect them from oxidative stress. Methodology: A randomized placebo-controlled clinical trial was conducted with the Oligocare Forte Plus tablet in treating oligospermia in subfertile males. Reduction in DNA fragmentation index % (DFI) was assessed at baseline and day 90 along with the pregnancy incidences amongst the couple enrolled for study. Results: Subjects with initially elevated DFI demonstrated a significant decrease post intervention. Among those with DFI >20%, Oligocare Forte Plus group witnessed an 18.63% reduction versus 12.63% in the placebo group. For DFI >40%, the decrease was 44.84% with Oligocare Forte Plus compared to 26.87% with placebo. The Oligocare Forte Plus group exhibited more incidence of pregnancy. Notably, there were no instances of premature subject discontinuation. Throughout the study, no adverse events or abnormalities were reported, indicating the safety and favorable tolerance of the Oligocare Forte Plus tablet. Conclusion: The current study serves as a confirmatory examination of the efficacy of Oligocare Forte Plus for the treatment of Oligoasthenoteratozoospermia, aiming to establish its viability as a therapeutic option before considering Intrauterine Insemination, Assisted Reproductive Technologies, or In Vitro fertilization procedures.